Inverted Patterns of Schistosomiasis and Fascioliasis and Risk Factors Among Humans and Livestock in Northern Tanzania - Ephrasia A. Hugho; Yakob P. Nagagi; Lucille J. Lyaruu; Victor V. Mosha; Ndealilia Senyael; Magweiga M. Mwita; Ruth W. Mabahi; Violet M. Temba; Mapulish Hebel; Mohamed Nyati; Blandina T. Mmbaga; Theonest O. Ndyetabura; et al. (Pathogens)
Fascioliasis and schistosomiasis are parasitic trematodiases of public health and economic concern in humans and livestock. However, data on the distribution and risk factors for fascioliasis remain limited, while epidemiological gaps hinder schistosomiasis control in Tanzania. This One Health, cross-sectional study examined the prevalence and risk factors of schistomiasis and fascioliasis in northern Tanzania, involving 310 livestock and 317 human participants from Arusha, Kilimanjaro, and Manyara regions. Using standard parasitological methods, livestock fascioliasis prevalence was 21.3%, while schistosomiasis prevalence was 1.0%. Human fascioliasis prevalence was 1.9%, while schistosomiasis prevalence was 12.6%. Female animals, particularly cattle in Kilimanjaro and Manyara, had higher odds of fascioliasis. Human–animal contact through husbandry increased schistosomiasis risk (aOR = 4.21; 95% CI: 1.81–9.80), while the use of borehole-water was protective (aOR = 0.33; 95% CI: 0.11–0.97). Fascioliasis risk was higher among individuals aged 36–55 years (aOR = 7.66; 95% CI: 1.36–43.23), with cabbage consumption offering protection (aOR = 0.08; 95% CI: 0.01–0.89). The study revealed inverted prevalence patterns of fascioliasis and schistosomiasis in humans and livestock, driven by vector-dependent transmission dynamics. These findings emphasize the need for an integrated One Health approach to manage shared human and animal health risks in Tanzania.